1991
DOI: 10.1128/mmbr.55.4.561-585.1991
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress responses in Escherichia coli and Salmonella typhimurium.

Abstract: INTRODUCTION AND SCOPE OF REVIEW been shown to cause damage to DNA, RNA, protein, and lipids. Active oxygen species are produced as an ines-Oxidative stress can be functionally defined as an excess capable by-product of normal aerobic metabolism, and their of prooxidants in the cell. Active oxygen molecules have production is further enhanced by exposure to certain environments or by dietary or disease conditions. Oxygen toxicity results wh~en the-degree of oxidative stress exceeds the * Corresponding author. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
373
0
10

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 675 publications
(401 citation statements)
references
References 162 publications
18
373
0
10
Order By: Relevance
“…The yeast Saccharomyces cerevisiae exhibits two distinct protective responses to hydrogen peroxide and to O-generating agents (Jamieson, 1992;Flattery-O'Brien et al, 1993). Such distinct, but overlapping, responses were previously known in bacteria (Demple and Halbrook, 1983;Christman et al, 1985;Greenberg and Demple, 1989), where more information has become available about the actual sensors of oxidative stress (Demple, 1991;Farr and Kogoma, 1991).…”
Section: Introductionmentioning
confidence: 72%
“…The yeast Saccharomyces cerevisiae exhibits two distinct protective responses to hydrogen peroxide and to O-generating agents (Jamieson, 1992;Flattery-O'Brien et al, 1993). Such distinct, but overlapping, responses were previously known in bacteria (Demple and Halbrook, 1983;Christman et al, 1985;Greenberg and Demple, 1989), where more information has become available about the actual sensors of oxidative stress (Demple, 1991;Farr and Kogoma, 1991).…”
Section: Introductionmentioning
confidence: 72%
“…In plants and animal phagocytic cells, the generation and release of AOS are thought to be important components of the host's immunity against bacterial infections. Pathogens have developed effective systems to counteract the resulting oxidative stress (for review, see [132]). For example, mutant bacteria defective in resistance to oxidative stress have been shown to be avirulent [133].…”
Section: Function In Host-pathogen Interactionsmentioning
confidence: 99%
“…and other Gram-negative bacteria is well known and the regulation and environmental role of these enzymes have in many cases been studied (e.g. [6,9,10]). In the present study, it was demonstrated that all the AOB studied possessed both catalase and SOD activity, but in very di¡erent proportions between strains (Table 1).…”
Section: Occurrence Of Oxidative Stress Enzymes In Aobmentioning
confidence: 99%